HAK ASASI MANUSIA MENURUT AL-QUR'AN DAN HADIS NABI SAW - Muhammad Zaini (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2016)
Human Rights at this time has become the center of international attention and become a hot issue and a lot of discussion. Although in Islam human rights not specifically have a charter, but al-Qur'an and Sunnah to focus on human rights. Prophet Muhammad from the beginning has been to implement the principle of religious freedom in the form of the principle of equality and respect for human beings in the medina very heterogeneous society as stipulated in the charter of the medina.